Evaluation of the Intrinsic Pathway of Coagulation in a Sample of Iraqi Patients with Acute Myocardial Infarction - Alwash, Maysem Mouayad; Alwash, Maysem Mouayad; Alqasim, *Alauldeen Mudhafar Zubair; Hammodi, Salim R. (AL-Kindy College Medical Journal, 2016)
Background: Acute myocardial infarction (AMI) is one of the most common diagnoses in hospitalized patients. Increased plasma hemostatic markers were noted in acute myocardial infarction, indicating that the blood coagulation system is highly activated in those patients. Aims of the study: To study the level of intrinsic coagulation factors including (FVIII:C, FIX:C ,FXI:C ,FXII:C ) in patients with acute myocardial infarction. Type of the study: Cross –sectional study. Methods: Thirty patients (their age range is 48-68 years) were included in this study (9 female, 21 male) who were just admitted to the coronary care unit in AL-Yarmouk Teaching Hospital and diagnosed as having acute myocardial infarction patients, blood samples were taken from those patients . Twenty healthy subjects (6 female, 14 male) age and sex matched with the patients were included as a control group. The following investigations were done for both groups: 1.Packed cell volume(PCV%) .by microhaematocrit method. 2.FVIII:C assay. [ by parallel line bioassay of coagulationfactors]. 3.FIX:C assay. 4.FXI:C assay. 5.FXII:C assay. Results Mean FVIII:C (162.63%±17.22)was significantly (P value< 0.05)higher in patients with acute myocardial infarction than control group(94.70%±9.34).1-Mean FIX:C (151.20%±14.20) was significantly (P value